2020
DOI: 10.5194/gmd-13-1685-2020
|View full text |Cite
|
Sign up to set email alerts
|

COSMO-BEP-Tree v1.0: a coupled urban climate model with explicit representation of street trees

Abstract: Abstract. Street trees are more and more regarded as an effective measure to reduce excessive heat in urban areas. However, the vast majority of mesoscale urban climate models do not represent street trees in an explicit manner and, for example, do not take the important effect of shading by trees into account. In addition, urban canopy models that take interactions of trees and urban fabrics directly into account are usually limited to the street or neighbourhood scale and hence cannot be used to analyse the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 122 publications
1
19
0
Order By: Relevance
“…This problem is typical not only for TERRA_URB, but also for more comprehensive UCMs such as DCEP in COSMO [95] and various schemes in WRF [96,97]. On the other hand, several studies have already demonstrated the noticeable impacts of explicitly accounting for urban vegetation in UCMs [98,99]. Thus, our study highlights the importance of the accurate ISA definition taking into account urban vegetation, and calls for more attention to urban vegetation in further UCM developments.…”
mentioning
confidence: 73%
“…This problem is typical not only for TERRA_URB, but also for more comprehensive UCMs such as DCEP in COSMO [95] and various schemes in WRF [96,97]. On the other hand, several studies have already demonstrated the noticeable impacts of explicitly accounting for urban vegetation in UCMs [98,99]. Thus, our study highlights the importance of the accurate ISA definition taking into account urban vegetation, and calls for more attention to urban vegetation in further UCM developments.…”
mentioning
confidence: 73%
“…Calculation of the plant canopy transpiration rate is based on the Jarvis-Stewart model in the form described in Daudet et al (1999) and Ngao et al (2017). Namely, the evaporation rate from the leaf surface E r is computed as…”
Section: Evapotranspiration and Latent Heat In Plant Canopy Modelmentioning
confidence: 99%
“…Urban forest governance under climate change has been mostly conceptualised within broader developments in urban sustainability and climate governance. However, there have also been efforts for creating specific frameworks regarding the climate-city-forest nexus [4], [33], [45], tailored decision-support software [25], [40], scenario modelling and simulations [27], [35]. Thus, it is possible to see the emergence of a more systematic understanding of urban forests and their peculiarities under climate change.…”
Section: Knowledge Integration For Better Decision-makingmentioning
confidence: 99%